Supply Chain Cost Prediction for Prefabricated Building Construction under Uncertainty. (18th October 2018) - Wang, Shaoli; Mursalin, Yasir; Lin, Gang; Lin, Conghua
Abstract : This paper considers the problem of predicting a supply chain cost for prefabricated building construction under an uncertain situation. Based on the Activity-Based Costing (ABC) method, we establish a computational model to estimate the total cost of the prefabricated supply chain. The model can assist in not only finding the critical areas for cost reduction of the whole supply chain but also analyzing other costs of prefabricated construction projects. Furthermore, we provide a numerical example of prefabricated building construction to validate the results.